Congestion management in power systems – A review. (September 2015) - Pillay, Anusha; Prabhakar Karthikeyan, S.; Kothari, D.P.
Highlights: The cost free and non cost free measures of congestion management in power systems are brought under one platform. Application of Genetic Algorithm, PSO and Bacterial Foraging Algorithm is discussed. Various new approaches like demand response management for managing congestion are embodied. A method of combined cumulants and Gram–Charlier expansion (CCGCE) is presented for congestion management in hybrid environment. Abstract: In the past few decades, restructuring has overtaken all possible domains including the electric supply industry. Restructuring has brought about considerable changes by the virtue of which electricity is now a commodity and has converted into deregulated one. Such a competitive market has paved way for innumerable participants. This has led to overloading and congestion of transmission lines. Moreover, open access transmission network has ingenerated a more intensified problem of congestion. Thus, congestion management in power systems is germane and of central importance to the power industry. In this paper a review work is carried out to unite all the publications in congestion management.